If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 = 28 + 5x Reorder the terms: 1 + 3x = 28 + 5x Solving 1 + 3x = 28 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + 3x + -5x = 28 + 5x + -5x Combine like terms: 3x + -5x = -2x 1 + -2x = 28 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + -2x = 28 + 0 1 + -2x = 28 Add '-1' to each side of the equation. 1 + -1 + -2x = 28 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 28 + -1 -2x = 28 + -1 Combine like terms: 28 + -1 = 27 -2x = 27 Divide each side by '-2'. x = -13.5 Simplifying x = -13.5
| 63=.5(2x^2+10x+6x+30) | | 0=X^2-12x+7 | | 34/100x16 | | H(t)=-4.9t^2+500t+200 | | x^2-2x+2=17 | | 5/6/3/1 | | 2(12x+2)+(15+2x)=74 | | Y=3/4x-20 | | x+0.05x=76.06 | | -3t^2+500t+200= | | 7w/5=-14 | | 0.05x+x=44 | | -4/9=x/108 | | 1.5x=44 | | -5u=10/3 | | 110=.5(x+5)(2x+12) | | x^2+.12x-.0156=0 | | 7x+13(18-x)=9(18) | | 3X=(x+6) | | 2x+2-4=0 | | f(x)=5x^2+30x+4 | | 6(x-15)=246 | | 4(3)+y=-10 | | 4x+(-2)=-10 | | -20+y=-10 | | −6=5x22/−3 | | 0=x^2+11x-80 | | 5m+1=6m-6 | | 15cm=3h/2 | | sin(6x)cos(11x)-cos(6x)sin(11x)=0.1 | | -2x(3)=5 | | r+14=7+r |